Character Building Of Students' Interests And Talents Through Learning Pop Music In The Field Of Cultural Arts - Ahmad Fauzan Yusman; Neviyarni Suhaili (SENDRATASIK UNP, 2021)
This article discusses the character arrangement of students, in this case students, from learning pop music to students. Compiled with quantitative methods with literature review. The main problem here is that there are too many types of music available at this time, one of which is pop music. In this day and age, pop music has been worldwide from an early age until adults love pop music, thus allowing pop music to be well received. Learning the art of music in services is to provide direct experience in the learning process for students, including other learning such as literature and language learning, skills and others. The formation of student character by learning pop music will determine the character of students from each song in pop music. In the 2013 curriculum, several materials were stipulated that support teachers to provide opportunities for students to develop character through learning pop music, including in the subject of Cultural Arts for junior high school level.